When dinosaurs go to school - Martin, Linda, 1961- (San Francisco : Chronicle Books, 2002)
Dinosaurs spend a day at school with reading, writing, arithmetic, music, fingerpaints, exercise, and pizza.
Booklist
Kirkus Review
3.8
K-3
K-3
Keywords: Dinosaurs -- Fiction; Schools -- Fiction; Stories in rhyme; Dinosaurs -- Fiction; School stories; Stories in rhyme